Improving Appointment Adherence among Young Adults with HIV in Peru with an mHealth Intervention: a Feasibility Study. (4th October 2017) - Prochazka, Mateo; Batey, D Scott; Zinski, Anne; Dionne-Odom, Jodie; Otero, Larissa; Rodriguez, J Martin; González, Elsa
Abstract: Background: Mobile Health (mHealth) interventions, including short message services (SMS) reminders and motivational messages, are associated with improved HIV appointment adherence, though feasibility is context-dependent. We assessed the feasibility of an mHealth intervention to improve appointment adherence among young adults with HIV in Lima, Peru. Methods: Between November 2016 and April 2017, we implemented a one-way mHealth pilot intervention in an outpatient hospital without electronic medical records. We enrolled young adults (age 18–29) entering HIV care in a 3-component intervention: (i) reminder SMS prior to scheduled appointments (provider, laboratory, pharmacy); (ii) motivational SMS after each visit; and (iii) phone call following a missed visit. Feasibility evaluation included enrollment acceptance, visit tracking (information captured in the study database within 3 days of attendance), and proportion of intervention delivery (threshold >90%). We performed a qualitative assessment to identify implementation challenges reviewing staff field notes and meeting minutes. Results: We enrolled 80/94 (85.1%) eligible participants. The median age was 25 years and 83% were male. The median time of follow-up after enrollment was 115 [interquartile range (IQR): 84–141] days, and participants had a median of 10 (IQR: 8–14) visits during the study period. Among 850 total participant visits, study personnel tracked 751 (88.4%); most (80.8%) untracked visits were pharmacy pickups. Of all tracked visits, most (78.7%) were scheduled appointments and 160 (21.3%) were unscheduled walk-ins. Intervention delivery reached 556/591 (94.1%) for reminder SMS; 733/751 (97.6%) for motivational messages, and 169/170 (99.4%) phone calls for missed visits, 127 (75.1%) of which were answered. Qualitative assessment revealed 2 major themes: real-time appointment tracking in a paper-based system consumed most staff time and resources, and meticulous in-person coordination between the implementation and hospital staff was essential for tracking. Conclusion: An mHealth intervention to improve appointment adherence among young adults with HIV in Peru appears feasible with dedicated staff and a reliable appointment tracking system. Digitalized appointment systems may be needed to address challenges for scale-up. Disclosures: All authors: No reported disclosures.